Keanekaragaman Arthropoda pada Pertanaman Sawi yang Diberi Perlakuan Penyemprotan Ekstrak Akar Tuba (Derris elliptica L.) - Toni Suryanto; Akhmad Gazali; Untung Santoso (Agroekotek View, 2020)
Organism disturbing plant is commonly found in the area of mustard planting that causes of losing production. The attempt to overcome organism disturbing plants to prevent using environmental pest control as an alternative substitute for chemical pesticides. The tuba plant (Derris elliptica L.) is one of the plant that can be used for biopesticide that has a compound poison called Rothenon (C22H2306). The purpose of this study is to know how the effect of several doses of the tuba root extract (Derris elliptica L.) in the level of arthropod diversity and determine the doses of the tuba root extract to produce highest of index diversity (H’) on a mustard green plant. The study was carried out at Experimental Field of the Faculty of Agriculture Lambung Mangkurat University on Banjarbaru, South Kalimantan From May – July 2018. Diversity is determined with the index of diversity (H’) Shannon-Wienner, the evenes of the index (E), the richness of index (R) and the domination of index (C). The design of this research is to use a completely randomized design consisting of 1 factor with 5 treatment. The research of this study indicates of the highest arthropod diversity is to T0 (0 g/l) of 2,53 and the lowest result is to T5 (8 g/l of water) at 2,16. The evenes index (E) and the richness index (R) of all treatment have steady dissemination of elevated index and the value of index domination  (C) is close to zero which means there are no species dominating this field research. The sprayed pesticide on the mustard green plant was affected by the percentage of leaf damage, by using a dose of 4g/l of water was able to give a real result to the wet weight it causes the whole treatment has been given the same dosage of manure.